Heaven, my home eaudiobook - Locke, Attica (Highway 59, 2019)
In this "captivating" crime novel ( People ), Texas Ranger Darren Mathews is on the hunt for a missing child — but it's the boy's family of white supremacists who are his real target. 9-year-old Levi King knew he should have left for home sooner; now he's alone in the darkness of vast Caddo Lake, in a boat whose motor just died. A sudden noise distracts him - and all goes dark. Darren Mathews is trying to emerge from another kind of darkness; after the events of his previous investigation, his marriage is in a precarious state of re-building, and his career and reputation lie in the hands of his mother, who's never exactly had his best interests at heart. Now she holds the key to his freedom, and she's not above a little maternal blackmail to press her advantage. An unlikely possibility of rescue arrives in the form of a case down Highway 59, in a small lakeside town where the local economy thrives on nostalgia for ante-bellum Texas - and some of the era's racial attitudes still thrive as well. Levi's disappearance has links to Darren's last case, and to a wealthy businesswoman, the boy's grandmother, who seems more concerned about the fate of her business than that of her grandson. Darren has to battle centuries-old suspicions and prejudices, as well as threats that have been reignited in the current political climate, as he races to find the boy, and to save himself. A Best Book of the Year New York Times Houston Chronicle NPR Wall Street Journal Milwaukee Journal-Sentinel Book Page Financial Times Kirkus SheReads Sunday Times LitHub Guardian Book Riot South Florida Sun Sentinel Longlisted for the Orwell Political Fiction Book Prize